A frequency control strategy of distributed photovoltaic cluster based on EMPC - WEI Wanjun; LIU Yi; PEI Kai; FANG Dezhi (Zhejiang dianli, 2023)
To enhance the integration of solar power generation into the grid and harness the frequency regulation capabilities of distributed solar photovoltaics， a distributed photovoltaic cluster frequency control strategy based on EMPC （extended model predictive control） algorithm is introduced. Firstly， a fuzzy subspace clustering algorithm that takes account of cluster voltage stability and auxiliary frequency regulation performance is employed. Appropriate clustering indicators are selected to divide large-scale distributed photovoltaic units into distributed photovoltaic clusters based on these indicators. Next， based on the clustering results， a model for the distributed photovoltaic cluster is constructed. State expansion variables are introduced to obtain a dynamic predictive model for the system’s frequency response. An EMPC objective function that considers the output prediction error of the distributed photovoltaic cluster and the cluster control increment is designed to perform rolling optimization and feedback correction of the model. Finally， simulation analysis is conducted under various operating conditions. The results demonstrate that the proposed control strategy can enhance the frequency support capability of distributed photovoltaic clusters when integrated into the grid and reduce power losses in the system.